Persepsi terhadap pengetahuan teknologikal pedagogi isi kandungan dalam kalangan guru sains sekolah rendah di Kelantan - Shukri, Ismail (2016)
Teacher readiness to integrate Information and Communication Technology (ICT) in teaching and learning is crucial in the 21st century and among the most important element in Science education. Technological Pedagogical Content Knowledge (TPACK) is a form of teacher knowledge related to technology integration of content and pedagogy. To date, there is no precise definition of TPACK constructs, and there is no instrument to measure the readiness of TPACK in the context of science teachers in Malaysia. Thus, the objective of this study was to obtain a holistic definition of TPACK and to verify the applicability of TPACK instruments among primary school science teachers in Malaysia. Three stages were involved: an initial survey of 60 teachers to obtain the constructs and start-up items, a three-round modified Delphi technique involving 16-panel experts to refine and validate the items, and a survey of 800 in-service teachers to validate the instrument. Data was analyzed based on the median and interquartile deviation (IQD) to get consensus from the experts. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were run to confirm TPACK items and constructs. Next, Regression Analysis was conducted to confirm the predictive validity of the instrument with the Level of Technology Integration Instrument (LoTI). The final number of items was 40, based on six valid constructs namely Pedagogical Knowledge (PK), Technological Knowledge (TK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), and Technological Pedagogical Content Knowledge (TPACK). All constructs provide a significant contribution to the level of technology integration. Results of the Multivariate Analysis of Variance (MANOVA) showed significant differences in gender, academic level, and teaching experience. The instrument developed in this study can be used to assess the level of preparedness of primary school science teachers to technology integration in the classroom in Malaysia.